Preoperative continuation vs. discontinuation of angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers on early cognitive function in elderly patients undergoing noncardiac surgery: a randomized controlled trial - Wang, Xiaohan; Yan, Yanan; Liu, Yurong; Xu, Chun; Zhuang, Jingwen; Wang, Zhiping (Frontiers in Aging Neuroscience, 2025)
ObjectivesTo evaluate the effect of preoperative continuation vs. discontinuation of angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs) on early cognitive function in elderly patients undergoing noncardiac surgery.MethodsThis prospective randomized controlled study was performed at the Affiliated Hospital of Xuzhou Medical University. Elderly patients aged 65 years or older, scheduled for elective noncardiac surgery under general anesthesia, and receiving long-term ACEI/ARBs therapy were randomly assigned to either continue or discontinue ACEI/ARBs therapy on the morning of surgery. The primary outcome was postoperative early cognitive function, assessed via neuropsychological tests including Auditory Verbal Learning Test-Huashan (AVLT-H), Clock Drawing Test (CDT), Number Connection Test (NCT), and Digit Span Test (DST) preoperatively and on postoperative day 1 (POD1). Secondary outcomes included intraoperative hypotension, use of phenylephrine, intraoperative fluid administration, incidence of hypertension, and length of hospital stay.ResultsThe NCT scores in the discontinued use of ACEI/ARBs group showed a significant decline on POD1 compared to baseline (p = 0.038). Both groups exhibited an increase in immediate recall scores from preoperative to POD1 (p = 0.003 and p = 0.002, respectively). The continued use of ACEI/ARBs group showed an increase in short-delayed recall (p = 0.007). However, there were no significant differences between the two groups (p > 0.05). The discontinued ACEI/ARB group had fewer episodes of intraoperative hypotension (p = 0.037) and lower requirements for phenylephrine (p = 0.016), despite a higher incidence of preoperative hypertension (p = 0.012). The continued use group received a larger volume of crystalloid fluids during surgery (p = 0.020). No significant differences were observed between the groups in the volume of colloid fluids administered (p > 0.05). There were no significant differences in postoperative hypertension or length of hospital stay between the groups (p > 0.05).ConclusionPreoperative continuation or discontinuation of ACEI/ARBs did not significantly affect early postoperative cognitive function in elderly patients.